2013
DOI: 10.1148/radiol.13120005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lung Inflation Level on Hyperpolarized3He Apparent Diffusion Coefficient Measurements in Never-Smokers

Abstract: Purpose:To evaluate the effects of lung volume differences on apparent diffusion coefficient (ADC) measurements on a regional basis, with breath holds at volumes adjusted for differences in lung size across individuals according to the subject's vital capacity (VC). Materials and Methods:This study was approved by the local institutional review board and was compliant with HIPAA. Informed consent was obtained from all subjects. Imaging was performed under a physician's Investigational New Drug application from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…As no ionizing radiation is associated with MR imaging, the method would be particularly attractive for examinations in children and pregnant women and when repetitive examinations are required. To introduce the method into clinical practice, the methodology of volume control becomes pivotal and would require standardization, as significant differences in lung microstructure with lung inflation level have been observed (41).…”
Section: Discussionmentioning
confidence: 99%
“…As no ionizing radiation is associated with MR imaging, the method would be particularly attractive for examinations in children and pregnant women and when repetitive examinations are required. To introduce the method into clinical practice, the methodology of volume control becomes pivotal and would require standardization, as significant differences in lung microstructure with lung inflation level have been observed (41).…”
Section: Discussionmentioning
confidence: 99%
“…ADC is regarded as a surrogate for localized airway or acinar dimensions, and can be calculated for each voxel to construct a semi-quantitative ADC map (Figure 5). Regional ADC changes have been observed in response to increases in lung volume [162, 163], gravity dependence [162, 164, 165], age [166], and emphysema in chronic obstructive pulmonary disease (COPD) or α-1-antitrypsin deficiency [121, 164, 167, 168]. ADC values for 129 Xe are lower than those of 3 He by an order of magnitude due to the higher density of 129 Xe gas (Table 1).…”
Section: Deriving Functional Measures From Hyperpolarized Agentsmentioning
confidence: 99%
“…Previous studies using diffusion‐sensitization gradients applied in one direction demonstrated heterogeneity of ADC values in healthy lungs, most notably a gradual increase in ADC in the craniocaudal and (subject posture‐dependent) anteroposterior directions, likely reflecting gravity‐dependent variations in alveolar size. Nonetheless, Halaweish et al demonstrated that the anteroposterior ADC gradient essentially disappears at total lung capacity, as used for all images collected in our study.…”
Section: Discussionmentioning
confidence: 98%